A COMPREHENSIVE REVIEW OF PETROLEUM-DERIVED PRODUCTS, REFINING PROCEDURES, AND CRUDE OIL FRACTIONS - Hussein Muteb Hatam; Ola Abdulhay Ali; Ayaat Khamess Ftekan (CHEDS: Journal of Chemistry, Education, and Science, 2026)
Petroleum,  known as crude oil in many countries is a non-renewable resource. It's a naturally-occurring liquid that exists beneath the Earth’s surface (lithosphere) and can potentially be extracted as an alternative fuel. Petroleum is a fossil fuel, having been made from the remains of dead plant and animal matter that was trapped under layers of sediments over millions of years. It forms in sedimentary rock where the heat and pressure is extreme. An example of a process that can demonstrate these principles is the cracking of crude oil into many useful fractions, including gasoline and its sisters in distillation known as "middle distillates" (see Petroleum Act) such as kerosene and diesel fuel: which is petroleum, a mixture of hydrocarbons between C1 to C50 Some characteristics are properties I think.and depending on one's location it may contain many chemical or physical differences. In this lesson, we discussed fractional distillation to obtain various products of petroleum from crude oil and its compositions